2018
DOI: 10.1186/s13014-018-1099-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor-infiltrating lymphocytes in patients with operable tongue cancer

Abstract: BackgroundOur aim was to investigate the prognostic significance of tumor-infiltrating lymphocytes (TILs) in operable tongue cancer patients.MethodsThe presence of CD3+, CD4+, CD8+, and forkhead box protein P3-positive (FOXP3+) TILs in tumor tissues obtained from 93 patients during surgery was examined using immunohistochemistry.ResultsThe 3-year overall survival (OS) of patients with a low CD8/FOXP3 ratio was significantly lower than that of patients with a high CD8/FOXP3 ratio (63.8% vs. 87.3%, p = 0.001). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…This finding confirms and underlines the well-known antitumoral effect of CD8 + T killer cells, which was observed in several solid cancers (23,24,40,(65)(66)(67). As previously shown by Chen (39) and now validated by our data, in OSCC, not only infiltration density of TIL subsets but also ratio of TILs, particularly CD8s:CD4s ratio, is of crucial impact in patient outcome and could potentially be taken into account when considering patient prognostication and treatment stratification.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding confirms and underlines the well-known antitumoral effect of CD8 + T killer cells, which was observed in several solid cancers (23,24,40,(65)(66)(67). As previously shown by Chen (39) and now validated by our data, in OSCC, not only infiltration density of TIL subsets but also ratio of TILs, particularly CD8s:CD4s ratio, is of crucial impact in patient outcome and could potentially be taken into account when considering patient prognostication and treatment stratification.…”
Section: Discussionsupporting
confidence: 90%
“…40). Especially in OSCC, a cancer exposed to an extensive microbial environment and noxae such as tobacco and alcohol within the oral cavity, Tregs potentially may inhibit harmful protumoral chronic inflammation (39,59). A hint to this explanation might be that in our cohort, stromal localization of Tregs was correlated with outcome.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Patients with advanced stage tumors also had higher proportions of CD3 cells compared to CD4 or CD8 T cells, suggesting that progression of their disease correlated with a shift toward a more suppressive TME. Of critical importance, this study demonstrated that patients with a low ratio of CD8 and CD4 cells to Treg cells ultimately had a lower overall survival, regional recurrence‐free survival, and distant metastasis‐free survival . These findings correlate with previous studies showing that patients with nuclear localization of Treg's and overall high levels of Treg cells in both stroma and cancer nests were associated with increased risk of tumor recurrence and worse disease‐free survival, respectively .…”
Section: Role Of Immune Evasion In Tumor Development and Progressionsupporting
confidence: 87%
“…Malignancy was found to be associated with an increase in the total amount of infiltrating lymphocytes and a transition from T to B cells. Chen et al similarly examined the prognostic implications of the composition of tumor infiltrating lymphocytes based on subtype and found that tongue tumors with higher overall CD4 infiltration and higher ratios of CD4 cells compared to CD3 (pan‐T cells), CD8, and FOXP3 (Treg cells) were associated with absence of lymphovascular invasion, pointing to a potential role for CD4 tumor infiltrating lymphocytes in the prevention of early metastatic disease . Patients with advanced stage tumors also had higher proportions of CD3 cells compared to CD4 or CD8 T cells, suggesting that progression of their disease correlated with a shift toward a more suppressive TME.…”
Section: Role Of Immune Evasion In Tumor Development and Progressionmentioning
confidence: 99%